A review of blocking in volleyball: From the notational analysis to biomachanics - Lobietti, R. (Journal of Human Sport & Exercise, 2009)
This article reviews the state of art of the research concerning the biomechanics of blocking in volleyball. Since it is fundamental to link the "reality of the game" (what happens in the field) with laboratory simulations, the logic procedure to investigate this skill followed this progression: 1) the importance of block in the game was analyzed in terms of relationships with the match results. 2) Blocking footwork techniques were classified and data relative to the frequency of blocking to stop the opponents attack were collected and analysed. 3) Kinematical analyses of blocking techniques were performed in the laboratory of the Faculty of Exercise and Sport Science at the University of Bologna, Italy. These results allow coaches to adjust the tactic in the game, to differentiate the type of drills and to develop some special exercises to train players for the improvement of their blocking technique.